Development of Learning Management System For Nava Dhammasekha Teachers In Indonesia - Tri Suyatno; Sulaiman Sulaiman; Santi Paramita; Putri Cakkhavati; Aurel Vimalla Pannadayika; Ratna Paramitha (Cita konsultindo, 2026)
This study aims to develop and evaluate a Learning Management System (LMS) at STAB Negeri Raden Wijaya as part of higher education digital transformation. The research employed the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The results indicate that the developed LMS achieved a media validity score of 86.67%, categorized as highly valid. The system demonstrates strong design quality, well-structured learning content, and evaluation features that support learning transparency. The needs analysis score of 65.2% suggests the necessity for further development, particularly in terms of system personalization and flexibility. The LMS also implements a scaffolding strategy in content organization, which enhances students’ cognitive engagement. The integration of security systems through SSO and LDAP strengthens academic accountability. Overall, the LMS is considered feasible for implementation without major revisions. Nevertheless, its long-term sustainability depends on continuous support, including digital literacy improvement, ongoing training, and the optimization of learning analytics to support data-driven decision making